Increasing the Pressure‐Free Stripping Capacity of the Lithium Metal Anode in Solid‐State‐Batteries by Carbon Nanotubes. Issue 26 (31st May 2022) - Fuchs, Till; Haslam, Catherine G.; Moy, Alexandra C.; Lerch, Christian; Krauskopf, Thorben; Sakamoto, Jeff; Richter, Felix H.; Janek, Jürgen
Abstract: Lithium metal is the key anode material for solid‐state‐batteries as its successful implementation will drastically increase their energy and power densities. However, anode contact loss during stripping leads to dendrites upon plating and subsequent cell failure. Design strategies to mitigate these issues are crucial to enable the use of lithium metal anodes. This paper reports the dissolution kinetics of composite anodes made of lithium metal and carbon nanotubes (CNTs) with a garnet‐type solid electrolyte (SE). In addition to an enhancement of the effective diffusion within the anode, its dissolution is fundamentally changed from being 2D to 3D. By maintaining contact with the SE, the CNTs facilitate lithium transport to the interface, which yields more than 20 mAh cm −2  discharge capacity at 100 µ A cm −2  without the application of external stack pressure (> 1 MPa). Conclusions drawn from electrochemical data on the anode microstructure are validated using cryo‐focused‐ion‐beam scanning electron microscopy and correlated with the mechanical properties. Micro‐indentation, acoustic analysis, and stress–strain testing show that mechanical properties of the anode, like yield strength and hardness, are adjustable. Overall, it is shown that the mechanical and electrochemical properties of Li–CNT composite electrodes can be tailored to suit the requirements of a practical cell. Abstract : This work demonstrates the working principle of composite electrodes consisting of lithium and carbon nanotubes in contact with garnet solid electrolyte, Lithium lanthanum zirconium oxide. Detailed analysis with impedance spectroscopy, electron imaging, and mechanical testing, shows that these composites are superior to pure lithium if low stack pressure is applied during stripping.